Philippine Education: Situationer, Challenges, and Ways Forward - Aniceto C. Orbeta; Vicente B. Paqueo (Philippine Institute for Development Studies (PIDS), 2022)
While the Philippine education system is in the middle of profound changes with the passage of RA 10533 or the Enhanced Basic Education Act of 2013, the country was rudely awakened by the poor results in its maiden participation in the 2018 Program for International Student Assessment (PISA) which tested 15-year-old students. This result was confirmed further by 2019 Trends in International Mathematics and Science Study (TIMSS) results which tested grade four students. Everyone's question is: What happened to the Philippine education sector? This paper answers this question by describing the three education subsectors as answers to three questions, namely: (a) where each of the subsectors is in terms of their primary outcomes, (b) what the primary reasons are why the subsectors are currently in that state, and (c) what the recommendations are on the ways forward. This report draws mainly from research done by the authors at the Institute and occasionally those done by other authors. The assessment shows that the country still has high attendance rates at all levels compared to countries of similar development states. It is, however, facing the challenge of low quality on the average even if it also produces high-quality graduates, many of whom have been working in global labor markets for decades now. Another problem is that education outcomes reflect students' socioeconomic status rather than equalizing. Finally, the Pandemic, which forced the country to remote learning mode largely unprepared like many countries, introduced another set of challenges in addition to its pre-pandemic problems. The country needs to learn from these experiences, rely more on data, and build rigorously validated evidence on what works for our educational system using our experience as educational outcomes are highly context-sensitive.
Keywords: 330; Education; Philippines; Basic Education; TVET; Higher Education